“His cramped and claustrophobic brain”: Confinement and Freedom in John Wray’s Lowboy - Pascale Antolin (European Journal of American Studies)
This article shows that ambivalence is a major symbolic pattern in John Wray’s 2009 neuronovel Lowboy, and it affects the major aspects of the novel, including the characters’ identities and the narrative structure of the book. Ambivalence may refer either to the split personality of the schizophrenic hero (psychoanalytic approach) or to the structure of the brain (neurologic approach). Especially, ambivalence allows subversion to prevail and transform the main protagonist’s mental confinement into textual freedom. This is shown, first, by an analysis of the referential framework and its major references, space and time. Then the major genres Lowboy borrows from are analyzed: on the one hand, the neuronovel suggests a bildungsroman, on the other, a mystery novel. While Wray borrows conventions from both, he also revisits and revises them, thus asserting the specificity of his novel and his freedom from generic conventions. Eventually, the manipulation of representation will be examined through an analysis of the language of description, particularly the use of incongruous images in the sections where Lowboy is the focal character.